TEXTURAL ANALYSIS AND HYDRAULIC CHARACTERISTICS OF AJALI SANDSTONES OF UGBENE-AJIMA AND ENVIRONS IN ANAMBRA BASIN, SOUTHEASTERN, NIGERIA - Ezike, Ejiofor Chinedu; Aganigbo, Chigozie Ignatius (Advanced Journal of Environmental Sciences (AJES), 2024)
This study highlights the textural characteristics and hydraulic conductivity of sandstones of Ajali Sandstone in Ugbene-Ajima area (southeastern Nigeria). The investigation approach involved field sampling and collection of 8 sandstone samples from different outcrop locations followed by laboratory studies such as sieve analysis. Sieve analysis and textural studies show that the sandstones range of 0.647-1.616. Other parameters such as coefficient of uniformity (Cu) range from -27.5 to 6.83 (av. -10.25), while standard deviation (sorting) values of 0.603-1.022 (av. 0.972) imply moderately well sorted sediments. The sandstones are mostly platykurtic and negatively skewed indicating sand of fluvial origin ranging from channel floor, point bar to braided rivers, also suggesting moderately to high/turbulent energy conditions with presence of winnowing actions. The Ajali Sandstone porosity values range from 2%-54% (av. 28.312) and the hydraulic conductivity values of 16.89-103.06 (av. 45.87). These values of porosity and hydraulic conductivity are indications of high specific yield for the sandstone which release economic water quantity.